WONDERFUL INDONESIA FESTIVAL 2015 DI THAILAND SEBAGAI DIPLOMASI KEBUDAYAAN INDONESIA - Halifa Haqqi, Tatik Erma Lestariningsih, Christy Damayanti & (Transformasi, 2016)
The purpose of the research is to explain about Wonderful Indonesia Festival 2015 inThailand as Indonesian cultural diplomacy. The bilateral relationship between Indonesia andThailand started in 1950 and inaugurated in 1954. The bilateral relations between Indonesiaand Thailand harmonious impacting one of them succeed in organizing Wonderful IndonesiaFestival 2015 in Thailand.Sebagian aspects of cultural diplomacy in theory can be applied in theWonderful Indonesia Festival 2015 in Thailand .In addition, the cultural diplomacy through theWonderful Indonesia Festival 2015 in Thailand can improve Indonesia's image abroad.Keywords: Cultural, Diplomacy, Relationship, Festival